Talk It Out: A Conflict Resolution Program for Preschool Children with Speech and Language Impairments - Kiernan, Barbara; Gray, Shelley (Seminars in Speech and Language, 2013)
Talk It Out was developed by speech-language pathologists to teach young children, especially those with speech and language impairments, to recognize problems, use words to solve them, and verbally negotiate solutions. One of the very successful by-products is that these same strategies help children avoid harming their voice. Across a school year, Talk It Out provides teaching and practice in predictable contexts so that children become competent problem solvers. It is especially powerful when implemented as part of the tier 1 preschool curriculum. The purpose of this article is to help school-based speech-language pathologists (1) articulate the need and rationale for early implementation of conflict resolution programs, (2) develop practical skills to implement Talk It Out strategies in their programs, and (3) transfer this knowledge to classroom teachers who can use and reinforce these strategies on a daily basis with the children they serve.
Keywords: Preschool; conflict resolution; specific language impairment (SLI)